THE CORRELATION BETWEEN STUDENTS' KNOWLEDGE OF PHONETIC SYMBOLS AND ENGLISH PRONUNCIATION ACCURACY - Risna; Riswanto; Endang Haryanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The knowledge of phonetic symbols is often underutilized in English pronunciation learning, despite being a fundamental tool for understanding and producing speech sounds accurately. This study aimed to determine whether there is a significant correlation between students’ knowledge of English consonant phonetic symbols and their English pronunciation accuracy among fifth-semester students of the English Education Study Program at State Islamic University of Fatmawati Sukarno Bengkulu. A quantitative correlational approach was applied with 20 participants selected through purposive sampling. Data were collected using a 50-item multiple-choice Knowledge of Phonetic Symbols Test and an oral Pronunciation Accuracy Test assessed by two independent raters. Data were analyzed using Pearson Product-Moment Correlation through SPSS, preceded by Shapiro-Wilk normality and linearity tests. Results showed a correlation coefficient of r = 0.762 with a significance value of 0.000 (p < 0.05), indicating a statistically significant strong positive correlation. The coefficient of determination (r² = 0.581) revealed that 58.1% of the variance in pronunciation accuracy was explained by phonetic symbol knowledge. It can be concluded that students with greater knowledge of IPA consonant symbols tend to demonstrate higher pronunciation accuracy, highlighting the importance of systematic phonetic symbol instruction in English Education programs.